The relationship between psychosocial variables and measures of health status in fibromyalgia - Marilize du Plessis; Henry R. Steel; André T. Möller (South African Family Practice)
Background: Fibromyalgia is considered to be a multifactorial condition in which a number of biological and psychological variables interact. However, the exact pathogenesis and effective treatment of fibromyalgia are still unknown. In this study, the relationship between psychosocial variables of self-efficacy, helplessness, perceived social support, and pain-related beliefs and several measures of health status of patients with fibromyalgia were examined.